Towards an Automated Synthesis of a Real-time Scheduling for Cyber-physical Multi-core Systems - Geismann, Johannes; Pohlmann, Uwe; Schmelter, David (Proceedings of the 5th International Conference on Model-Driven Engineering and Software Development)
Modern Cyber-physical Systems are executed in physical environments and distributed over several Electronic Control Units using multiple cores for execution. These systems perform safety-critical tasks and, therefore, have to fulfill hard real-time requirements. To face these requirements systematically, system engineers de- velop these systems model-driven and prove the fulfillment of these requirements via model checking. It is important to ensure that the runtime scheduling does not violate the verified requirements by neglecting the model checking assumptions. Currently, there is a gap in the process for model-driven approaches to derive a feasible runtime scheduling that respects these assumptions. In this paper, we present an approach for a semi- automatic synthesis of behavioral models into a deterministic scheduling that respects real-time requirements at runtime. We evaluate our approach using an example of a distributed automotive system with hard real-time requirements specified with the MechatronicUML method.

The MechatronicUML Requirements Engineering Method: Process and Language - Holtmann, Jörg; Fockel, Markus; Koch, Thorsten; Schmelter, David; Brenner, Christian; Bernijazov, Ruslan; Sander, Marcel
In this technical report, we present the MechatronicUML requirements engineering method. The method encompasses a process and a scenario-based modeling language for the documentation and analysis of requirements on the message-based interaction behavior of software-intensive systems. The modeling language uses a scenario notation based on Modal Sequence Diagrams (MSDs), which borrows concepts of UML Interactions as well as of Live Sequence Charts. Furthermore, we introduce the so-called Emergency Braking & Evasion System (EBEAS) as a running example, which is based on current and upcoming real-world driver assistance systems.

Towards Feature-based Product Line Engineering of Technical Systems - Koch, Thorsten; Holtmann, Jörg; Schubert, David; Lindemann, Timo (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering (SysInt 2016))
The development of today’s technical products (e.g., in automation) is characterized by high customer expectations regarding the product individualization, which causes a wide range of product variants. Original equipment manufacturers (OEMs) can apply classical approaches from product line engineering, like feature modeling, to cope with the variability and the induced development complexity. Our tool support for feature models integrates a variety of feature model extensions like feature attributes and properties, logical constraints between features and feature properties, and the distinction between features and feature realizations. Furthermore, technical products have geometrical dimensions. The OEM specifies Computer Aided Design (CAD) models to consider these geometric dimensions and to virtually layout particular product variants. Geometric assembly constraints specify how parts of the product can be arranged in a CAD model. However, a potential product customer cannot configure an individual product variant and virtually layout this variant in the same software tool since the respective information stems from different sources. In order to cope with this problem, we present in this paper an extension of our tool support for feature models to specify geometric assembly constraints. Based on the proposed extension, we outline our research roadmap to consider these constraints in an online shop of an e-commerce system, in which a potential customer shall be able to configure a product variant and to virtually layout it according to the assembly constraints.

ASIL Tailoring on Functional Safety Requirements - Fockel, Markus (5th International Workshop on Next Generation of System Assurance Approaches for Safety-Critical Systems (SASSUR))
Cyber-physical systems like self-driving cars are highly complex and safety-critical. This results in a great number of safety requirements that have different levels of criticality. In automotive, the criticality is categorized in Automotive Safety Integrity Levels (ASIL). As a high ASIL causes high development effort, the goal is to develop most subsystems with lower ASIL requirements. To achieve this ASIL tailoring, subsystems need to be separated or redundantly implemented. These safety measures are usually integrated late in the development process and thus cause costly development iterations. In this paper, we present a systematic, tool-supported ASIL tailoring process for the requirements analysis phase. It is applied on formal safety requirements and automatically generated fault trees for a functional view of the system. The process supports early planning of safety efforts for mixed-criticality systems and avoids costly late development iterations.

Requirements Engineering - Zusatzaufgabe oder Kernkompetenz? - Holtmann, Jörg; Fockel, Markus; Koch, Thorsten; Schmelter, David (OBJEKTspektrum)
In verschiedenen Unternehmen wird mit Anforderungen unterschiedlich umgegangen. Je nach Größe, Branche und Unternehmenskultur ist das Thema Requirements Engineering (RE) mal weniger, mal mehr etabliert. In einigen Unternehmen wird es als lästige Zusatzaufgabe betrachtet, während andere Unternehmen ganze Abteilungen mit RE als Kernkompetenz betreiben. RE wird allerdings in jedem Projekt - bewusst oder unbewusst - durchgeführt! RE ist die Basis für den weiteren Entwicklungsprozess, die Validierung/Verifikation und die Plan- und Messbarkeit des Projekts. Darüber hinaus können Fehler, die auf Anforderungsebene gefunden werden, weniger aufwendig und somit günstiger behoben werden als in späteren Entwicklungsphasen. Am Fraunhofer IEM beraten wir Unternehmen und erforschen neue Methoden bezüglich der Entwicklung von intelligenten technischen Systemen. In diesem Artikel berichten wir über unsere Erfahrungen aus Projekten, in denen wir Unternehmen aus verschiedenen Branchen und mit unterschiedlichem RE-Reifegrad zwecks Leistungssteigerung des RE begleitet haben. Auf Basis dieser Projekterfahrungen zeigen wir Wege auf, wie der Stand des RE mittels eines Reifegradmodells im eigenen Unternehmen verbessert werden kann.

Integrated and iterative systems engineering and software requirements engineering for technical systems - Holtmann, Jörg; Bernijazov, Ruslan; Meyer, Matthias; Schmelter, David; Tschirner, Christian (Journal of Software Evolution and Process)
The development of software-intensive technical systems involves several engineering disciplines like mechanical, electrical, control, and particularly software engineering. Model-based Systems Engineering (MBSE) coordinates these disciplines throughout the development by means of discipline-spanning processes and a system model. Such a system model provides a common understanding of the system under development and serves as a starting point for the discipline-specific development. An integral part of MBSE is the requirements engineering on the system level. However, these requirements need to be refined for the discipline-specific development to start, e.g., into specific requirements for the embedded software. Since existing MBSE approaches lack support for this refinement step, we conceived in previous work a systematic transition from MBSE to model-based software requirements engineering. We automated the steps of the transition where possible, in order to avoid error-prone and time-consuming manual tasks. In this paper, we extend this approach with support for subsequent process iterations and provide an algorithm for the automated steps. We illustrate the approach and perform a case study with an example of an automotive embedded system.

Vom Systemmodell zu disziplinspezifischen Modellen und zurück - Schmitz, Joachim; Fockel, Markus (Tag des Systems Engineering 2015)
Zukünftige mechatronische Systeme entwickeln sich mehr und mehr zu intelligenten technischen Systemen, die durch eine zunehmende Verzahnung der mechanischen, elektrischen und informationsverarbeitenden Anteile gekennzeichnet sind. Um das Zusammenspiel der Disziplinen besser zu beherrschen, werden zunehmend Methoden und disziplinübergreifende Systemmodelle des Systems Engineering genutzt. Offene Probleme sind dabei noch die Nachverfolgbarkeit der Entwicklung (Traceability) und die Verwaltung zueinander konsistenter Versionen von disziplinübergreifenden und disziplinspezifischen Modellen. Dieser Beitrag adressiert diese Probleme durch die Verknüpfung der Spezifikationstechnik CONSENS für den Systementwurf mit dem Datenmanagementwerkzeug SYNECT. Der Beitrag stellt die Konzipierung und prototypische Werkzeugunterstützung für die Verknüpfung von Systemmodellen und disziplinspezifischen MATLAB/Simulink-Modellen vor.

Systementwurf unter Einbeziehung funktionaler Sicherheit bei automobilen Steuergeräten - Meyer, Jan; Fockel, Markus; Holtmann, Jörg (Tag des Systems Engineering 2015)
Automobile Steuergeräte realisieren mehr und mehr sicherheitskritische Funktionen. Nicht erst durch die Einführung der ISO 26262 werden an die Entwicklung sicherheitskritischer Funktionen besondere Anforderungen zum Beispiel in Form von Sicherheitsanalysen gestellt. In der Praxis hat sich herausgestellt, dass durch den bisherigen Systementwurf nicht alle notwendigen Daten für die Sicherheitsanalysen vorlagen. Von daher war eine Erweiterung des bisherigen Vorgehens erforderlich, sodass die benötigten Daten zu den erforderlichen Zeitpunkten vorliegen und die Sicherheitsanalysen ohne aufwendige Nacharbeiten erstellt werden können. Dieser Artikel beschreibt die durchgeführten Erweiterungen und die Erfahrungen, die in Serienprojekten eines automobilen Zulieferers gesammelt wurden.

ReqPat: Efficient Documentation of High-quality Requirements using Controlled Natural Language - Fockel, Markus; Holtmann, Jörg (Proc. of the 23rd International Requirements Engineering Conference 2015 (RE15))
The growing complexity of today's software intensive systems results in an increased size of requirements specifications, which are typically documented by means of natural language (NL). Large NL requirements specifications are prone to contain defects (e.g., contradictions), and the inherent ambiguity of NL impedes automatic techniques to support the requirements engineer. In order to cope with this problem, we conceived a requirements documentation approach implemented in the tool ReqPat. Using a controlled NL, it supports an efficient requirements documentation, an automatic requirements validation, and an automatic transition to models--while still keeping the requirements understandable for all stakeholders.

Integrated systems engineering and software requirements engineering for technical systems - Holtmann, Jörg; Bernijazov, Ruslan; Meyer, Matthias; Schmelter, David; Tschirner, Christian (Proceedings of the 2015 International Conference on Software and System Process)
The development of software-intensive technical systems (e.g., within the automotive industry) involves several engineering disciplines like mechanical, electrical, control, and software engineering. Model-based Systems Engineering (MBSE) coordinates these disciplines throughout the development by means of discipline-spanning processes and system models. Such a system model provides a common understanding of the system under development and serves as a starting point for the discipline-specific development. An integral part of MBSE is the requirements engineering on the system level. However, for the discipline-specific development to start, these requirements need to be refined, e.g., into specific requirements for the embedded software. Since existing MBSE approaches lack support for this refinement step, we conceived a systematic transition from MBSE to model-based software requirements engineering, which we present in this paper. We automated the steps of the transition where possible, in order to avoid error-prone and time-consuming manual tasks. We illustrate the approach with an example of an automotive embedded system.